2005
DOI: 10.1007/s00299-005-0927-y
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a cDNA probably encoding oxidosqualene cyclase associated with asiaticoside biosynthesis from Centella asiatica (L.) Urban

Abstract: A homology-based PCR method was used to clone a cDNA encoding oxidosqualene cyclase from Centella asiatica, which produces a large quantity of triterpene saponins such as asiaticoside and madecassoside. Sequence analysis of one clone found sequences related to beta-amyrin synthase. An open reading frame in the full-length clone was named CabAS (Centella asiatica putative beta-amyrin synthase). On the basis of amino acid sequence, CabAS appears to be an enzyme (beta-amyrin synthase) that synthesizes beta-amyrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…In contrast to our data, they could not detect asiaticoside in undifferentiated cells. Their results have shown that asiaticoside biosynthesis is concentrated in the leaves (0.4-1.4% dry weight) and that the level of asiaticoside content is quite low in the roots of whole plants (Kim et al 2002a(Kim et al , 2004(Kim et al , 2005(Kim et al , 2007.…”
Section: Resultsmentioning
confidence: 94%
“…In contrast to our data, they could not detect asiaticoside in undifferentiated cells. Their results have shown that asiaticoside biosynthesis is concentrated in the leaves (0.4-1.4% dry weight) and that the level of asiaticoside content is quite low in the roots of whole plants (Kim et al 2002a(Kim et al , 2004(Kim et al , 2005(Kim et al , 2007.…”
Section: Resultsmentioning
confidence: 94%
“…The results of several reports show that the gene transcriptions of squalene synthase, as well as squalene epoxidase and β-amyrin synthase associated with triterpene biosynthesis, are increased as a consequence of MJ treatment (Suzuki et al 2002, Hayashi et al 2003, Kim et al 2005. Lee et al (2004) demonstrated that PgSS transcription was observed at its highest levels in the adventitious roots of ginseng 24 h after MJ treatment.…”
Section: Expression Analyses Of Pgfps Mrnamentioning
confidence: 93%
“…In contrast, the expression level was highest in flower, and roots and hypocotyls in case of Nigella sativa (Scholz et al 2009) and Glycyrrhiza glabra (Hayashi et al 2001) respectively. In other reports, the accumulation of transcripts was higher in leaves of Gentiana straminea (Liu et al 2009) and C. asiatica (Kim et al 2005). …”
Section: Dryopteris Crassirhizoma Dds (Bag68223)mentioning
confidence: 55%